1972
DOI: 10.1111/j.1476-5381.1972.tb07259.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐lasting peripheral and central effects of 6‐hydroxydopamine in rats

Abstract: Summary1. In newborn rats treated with 6-hydroxydopamine hydrobromide (6-OHDA) (50-150 mg/kg on 5-7 days) a widespread and long-lasting dose related sympathectomy was demonstrated. 2. When rats given 6-hydroxydopamine (100 mg/kg, seven treatments) in the neonatal period were killed at 10 weeks the concentration of noradrenaline (NA) in the heart, mesentery and vas deferens was significantly reduced. There was no alteration in the catecholamine content of the adrenal glands. 3. The amplitude of the responses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(42 citation statements)
references
References 18 publications
(33 reference statements)
2
40
0
Order By: Relevance
“…injection of 6-OHDA. In very young rodents this treatment allows 6-OHDA to cross the immature blood-brain barrier and create a long lasting CA deficit, especially in the neocortex (Clark et al 1972;Sachs 1973;Sachs and Jonsson 1975). We succeeded in showing that this technique is also etfective for CA depletion in kitten cortex, but we found no loss of plastic response to monocular deprivation, even in kittens with less than 5% of normal NE levels in the neocortex (Bear et al 1983;Bear and Daniels 1983).…”
Section: Introductionmentioning
confidence: 63%
“…injection of 6-OHDA. In very young rodents this treatment allows 6-OHDA to cross the immature blood-brain barrier and create a long lasting CA deficit, especially in the neocortex (Clark et al 1972;Sachs 1973;Sachs and Jonsson 1975). We succeeded in showing that this technique is also etfective for CA depletion in kitten cortex, but we found no loss of plastic response to monocular deprivation, even in kittens with less than 5% of normal NE levels in the neocortex (Bear et al 1983;Bear and Daniels 1983).…”
Section: Introductionmentioning
confidence: 63%
“…The relative levels of noradrenaline are unlikely to be identical after acute administration directly into the brain with those obtained by chronic neonatal treatment and this makes interpretation of their results more difficult. Chronic systemic administration of 6-OHDA to neonatal rats produces a widespread and long-lasting depletion of noradrenaline in different regions of the brain, especially cortex, cerebellum and spinal cord (Clark et al, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that treatment with drugs that facilitate GABA transmission will ameliorate the behavioural signs of the HPNS, although these data do not indicate whether a decrease in GABA transmission occurs during the appearance of the HPNS. This paper describes experiments in which two compounds altering different neurotransmitter systems have been given both separately and together, the neurotoxin 6-hydroxydopamine (6-OHDA) which produces a permanent loss of noradrenergic terminals from those brain regions normally innervated by the dorsal noradrenergic bundle (Clark, Laverty & Phelan, 1972), and the GABA agonist, muscimol.…”
Section: Introductionmentioning
confidence: 99%
“…2, AUGUST 1979 to nerve growth factor (immunosympathectomy; Levi-Montalcini and Angeletti, 1966) or 6-hydroxydopamine (Angeletti and Levi-Montalcini, 1970). The chemical sympathectomy produced by the neonatal administration of 6-hydroxydopamine also has the disadvantage of producing marked effects on central noradrenergic neurons (Clark et al, 1972;Jacks et al, 1972), and hence, it does not produce a strictly peripheral sympathectomy. Both methods produce permanent sympathectomy only when administered to neonates.…”
mentioning
confidence: 99%